Effect of condensation conditions on phase formation in thin two-layer Ni/GaAs films - Grebennik, I.P.; Gladkikh, N.T.; Dukarov, S.V. (STC “Institute for Single Crystals”, 1998)
The temperature and structure state of substrate (NaCl poly- and single crystals) are shown to influence the structure of phases formed as a result of interaction between Ni and GaAs layers. In films on polycrystal substrates, polycrystal phases with structures similar to the γ-, γ'-, NiAs, Ni3Ga4 phases in Ni-Ga and Ni-As systems are formed besides the amorphous one. Single crystal substrate exerts an orienting influence resulting in the energetically favourable growth of the hexagonal phase of the triple system with parameters aγ''= aγ', cγ'' = 2cγ'. . . . . . . . . . . . . . . . . . . Показано, что температура и структурное состояние подложки (поли- и монокристаллов NaCl) оказывает влияние на структуру фаз, образующихся при взаимодействии слоев Ni и GaAs. На поликристаллических подложках в пленках, наряду с аморфной, образуются поликристаллические фазы, структура которых подобна фазам γ-, γ'-, NiAs, Ni3Ga4, в системах Ni-Ga, Ni-As. Монокристаллическая подложка оказывает ориентирующее действе и приводит к энергетически более выгодному росту гексагональной фазы тройной системы с параметрами aγ''= aγ', cγ'' = 2cγ'.
Keywords: Thin films; gallium arsenide; crystal structure; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces